Self-perceived oral health and associated factors among the elderly in Campinas, Southeastern Brazil, 2008-2009 - Silva, Débora Dias da; Held, Roberta Barros de; Torres, Stella Vidal de Souza; Sousa, Maria da Luz Rosário de; Neri, Anita Liberalesso; Antunes, José Leopoldo Ferreira (Revista de Saúde Pública, 2011)
OBJECTIVE: To describe self-perceived oral health among elderly people and assess associated sociodemographic and clinical factors. METHODS: A cross-sectional study was carried out with 876 participants forming a representative sample of elderly people (65 years of age or over) in Campinas, Southeastern Brazil, in 2008-2009. Dental examinations were conducted in accordance with criteria standardized by the World Health Organization for epidemiological surveys on oral health. Self-perceived oral health was evaluated using the Geriatric Oral Health Assessment Index (GOHAI). Individuals were classified according to sociodemographic characteristics, dental factors and prevalence of biological frailty. Associations were assessed using Poisson regression analysis, taking into consideration sample weights and the complex structure of the cluster sampling. RESULTS: The subjects' mean age was 72.8 years; 70.1% were women. The proportion of the individuals with more than 20 teeth present was 17.2%; 38.2% were using full dentures in both arches; 8.5% needed dental prostheses in at least one arch. On average, the GOHAI was high: 33.9 (maximum possible: 36.0). Retaining 20 teeth or more, using full dentures in both arches, not needing such treatment, not presenting any oral mucosa abnormalities and not presenting biological frailty were factors significantly associated with better self-perceived oral health (p < 0.05). CONCLUSIONS: Assessment of self-perceived oral health made it possible to identify the main factors associated with this outcome. This tool may contribute towards planning dental services and guide health promotion strategies for improving the quality of life of individuals within this age group.